2021
DOI: 10.1111/ggr.12371
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of 186Os/188Os Measurements by N‐TIMS Using Amplifiers Equipped with 1013 Ω Resistors

Abstract: Analysis of 186Os/188Os variations in most natural samples is hampered by their low Os mass fractions (usually < 100 pg g−1), requiring Os separation from up to a kilogram of powder to obtain high precision measurement results. Recently developed amplifiers equipped with 1013 Ω feedback resistors improve the signal to noise ratio by an order of magnitude, allowing acquisition of high precision data (2SE < 50 ppm) from 186Os16O3− ion beams of ~ 40 fA and thus analysis of less material (~ 10–500 g). Factors cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 29 publications
2
16
2
Order By: Relevance
“…Depending on the version, the amplifiers show different responses to any instrumental trouble in the constant current generator. This idea does not contradict with previous studies 17–19 that reported no systematic error in the isotopic data obtained by TIMS using the 3.3 pA constant current calibration.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Depending on the version, the amplifiers show different responses to any instrumental trouble in the constant current generator. This idea does not contradict with previous studies 17–19 that reported no systematic error in the isotopic data obtained by TIMS using the 3.3 pA constant current calibration.…”
Section: Resultssupporting
confidence: 77%
“…A new calibration technique for the 10 13 U Faraday amplier was recently reported to achieve better precision in gain measurement. [16][17][18][19] This technique employs a fully sowarecontrolled procedure that entails the use of a 3.3 pA constant current generator, while the automation of the calibration protocol tends to obscure technical or instrumental problems. In practice, our preliminary isotopic data yielded a systematic error of >0.1&, suggesting a need for the validation of the calibration protocol prior to an isotopic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1 1 0 signal filtering. Though our results fail to improve on the precision of previous procedures for determining Os isotopes, they indicate a role for amplifier gain factor uncertainty (Reisberg and Zimmermann 2021) and potentially Faraday Cup deterioration (Fukai et al 2017, Di et al 2021 as important contributors to Os isotope imprecision, and highlight the need for multi-dynamic Os isotope measurements.…”
contrasting
confidence: 86%
“…However, it is not possible to use multi-dynamic methods that measure 186 Os and 188 Os on the same cup with 10 12 Ω or 10 13 Ω amplifiers, as appropriate 186 Os signal intensities would likely saturate the 10 12 Ω amplifier during analysis of the second jump. The only case in which 10 12 Ω or 10 13 Ω amplifiers may be suitable for 186 Os determination in samples with low Os mass fractions (Reisberg and Zimmermann 2021), though the large associated uncertainties ($ 85 ppm) means their utility may be restricted to samples with high Pt/Os.…”
Section: Summary Of Uncertainties and Comparison With Dross Resultsmentioning
confidence: 99%
See 1 more Smart Citation